Performance analysis and analysis for performance : a study of Villa-Lobos's Bachianas Brasileiras No. 9 - Gerling, Fredi Vieira (2000)
This study of Villa-Lobos’s Bachianas Brasileiras No. 9 aims at gaining insight into the decision-making processes of translating a score into a musical performance. Chapter I presents a discussion of selected issues related to interpretative analysis. Chapter II is an overview of the approaches to recording comparison deemed relevant to the present study. Chapter III is a comparative study of the vocal and string versions of Bachianas Brasileiras No. 9, while Chapter IV offers a structural analysis of the work. Chapter V compares four recordings: the composer’s own with the Orchestre National de La Radiodiffusion Française—EMI 7243 5 66964 2 6; Odaline de la Martinez and the BBC Singers, LNT 102; Michael Tilson Thomas and the New World Symphony —RCA 09026-68538-2; and my own CD, Construção, Orquestra de Câmara Theatro São Pedro- Limited Edition (live recording made on December 11, 1995 in Bayreuth, Germany). This comparison utilizes data obtained with the software Tempo. The tabulation of these results is shown in graphs that compare how matters of tempo flexibility affect each performance. This multi-faceted study shows that although painstaking analysis can lead to insightful solutions, the fleeting nature of musical performance requires an open mind and imagination to deal with the often contradictory directives of the score.